SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA WISATA NAKNY FUNLAND - Sitorus, Wilona Edra Rachel; Hutapea, Marlyna Infryanty; Simanjuntak, Arthur (Universitas Methodist Indonesia, 2023)
One of the tourist attractions from Deli Serdang, North Sumatra, which recently went viral is Nakny Funland. Nakny Funland is frequently visited by local tourists and tourists from outside the region, however currently Nakny Funland still uses the manual method in its system, namely by recording a book system in the process of recording ticket sales and financial reports so there is a high probability that errors can occur in entering data, errors in calculations. data on tickets sold, errors in making financial reports, and can hamper the search process for the data needed. Therefore, we need an accounting information system that can produce faster and more accurate information. The author will create a ticket sales accounting information system at Nakny Funland Tourism using Microsoft Visual Basic 2010 as software and MySQL as database to process the data. The purpose of creating this system is to assist the performance of officers and persons in charge at Nakny Funland Tourism in making the process of recording ticket sales and financial reports easier, faster, and more accurate, and can minimize errors in making records.